[Urbach 5.]
1925-1963: Zoo in Budapest, boat-trip on the Danube, vacation in the Alps mountain, sailing on the Balaton, car race in the Városliget-1925, the Rózsadomb in Budapest, amateur sex film, a trip to Palást